Zarządzanie fraktalnymi strukturami systemów wytwórczych - Dudek, Marek (Management of Fractal Structures of Manufacturing Systems, 2009)
To meet the rapidly changing customer needs in the manufacturing environment, future manufacturing systems must be dynamically and flexibly reconfigured. The fractal manufacturing system is one of the new manufacturing concepts that can meet such requirements. Fractal manufacturing is an emerging concept that allocates the production resources into similar multifunctional cells capable of processing a wide variety of products. Fractal system is comprised of a number of basic components, each of which consists of five functional modules: an observer, an analyzer, an organizer, a resolver, and a reporter. Each of these modules, using agent technology, autonomously co-operates and negotiates with others while processing its own jobs. In this paper, the author suggests to make use of simulation models to chose one of the most profitable logical structures of fractal manufacturing system. The results indicate that the procedure is efficient and that model layout optimization can improve production flows.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 366-373